Revealing the Class-Gender Connection: Social Policy, Labour Markets and Households - Clement, Wallace (Just Labour: A Canadian Journal of Work and Society, 2004)
Comparative studies of welfare states are in the process of changing how they examine the relationships between class, gender and generations. Earlier accounts have focused on ideal types of regimes connecting social policy and labour markets. More recent accounts invoke families as key sites of investigation. The argument introduced here advocates for the combined connection between the intersections triad of social policy, labour markets and households as they reveal the relations embodied in class, gender and generation. Most of the illustrations locate households within the triad since they have received the least attention.